Lysophosphatidylcholine disrupts cell adhesion and induces anoikis in hepatocytes. Issue 4 (1st February 2022) - Chen, Hao; Ma, Jiarui; Liu, Jin; Dou, Lin; Shen, Tao; Zuo, Huiyan; Xu, Fangzhi; Zhao, Li; Tang, Weiqing; Man, Yong; Ma, Yanyan; Li, Jian; et al.
Abstract : Lysophosphatidylcholine (LPC), the active metabolite of palmitate, triggers hepatocyte death by activating endoplasmic reticulum stress and JNK signalling‐mediated lipoapoptosis. However, LPC‐induced cytotoxicity in hepatocytes is not well understood. Here, we found for the first time that LPC‐induced cell rounding occurred prior to apoptosis. LPC‐induced rounding of cells reduced both cell–extracellular matrix (ECM) adhesion and cell–cell junctions, which promoted detachment‐induced apoptosis (defined as anoikis) in hepatocytes. Further study revealed that LPC altered cellular morphology and cell adhesion by inhibiting integrin and cadherin signalling‐mediated microfilament polymerization. We also found that ECM supplementation and microfilament cytoskeletal stabilization inhibited LPC‐induced hepatocyte death by attenuating anoikis. Our data indicate a novel cytotoxic process and signalling pathway induced by LPC. Abstract : Under physiological conditions, the integrin and cadherin signalling pathway‐mediated microfilament network maintains the integrity of focal adhesion and adherens junctions and maintains the morphology of adherent cells. Treatment with lysophosphatidylcholine (LPC) disrupts integrin and cadherin signalling and, subsequently, induces microfilament depolymerization, leading to decreased cell–extracellular matrix adhesion and cell–cell junctions and induction of anoikis.